Innovations in Computer Science and Engineering Proceedings of the Third ICICSE, 2015 - Saini, H. S.; Sayal, Rishi; Rawat, Sandeep (Advances in Intelligent Systems and Computing, 2016)
The book is a collection of high-quality peer-reviewed research papers presented at the third International Conference on Innovations in Computer Science and Engineering (ICICSE 2015) held at Guru Nanak Institutions, Hyderabad, India during 7 - 8 August 2015. The book discusses a wide variety of industrial, engineering and scientific applications of the emerging techniques. Researchers from academic and industry present their original work and exchange ideas, information, techniques and applications in the field of Communication, Computing, and Data Science and Analytics.